1982
DOI: 10.1136/gut.23.12.1048
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric nitrites, nitrosamines, and bacterial overgrowth during cimetidine treatment.

Abstract: SUMMARY A six week course of cimetidine (1 g/day) healed peptic ulcers in 20 of 23 patients (14 with duodenal ulcer, nine with gastric ulcer). Reduction of basal acid output by 73% and peak acid output by 36% led to a rise in concentrations of intragastric aerobic bacteria and nitrate-reducing bacteria. While the mean intragastric concentration of nitrate was unchanged by treatment, there were statistically significant rises in nitrite and N-nitrosamine concentrations. The conversion from nitrates to nitrites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
6

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(46 citation statements)
references
References 20 publications
4
36
0
6
Order By: Relevance
“…The fact that patients with pernicious anemia, invariably associated with gastric atrophy and hypochlorhydria, have an increased risk of developing stomach cancer [52,53] has raised the question of whether therapeutic hypochlorhydria is carcinogenic to the stomach. Pharmacologically induced hypochlorhydria has been shown to be associated with increased gastric bacterial growth, reduction of nitrate to nitrite, and increased concentration of carcinogenic N-nitroso compounds in the gastric juice [54,55]. Some studies have indicated that long-term treatment with PPIs may accelerate the development of atrophic changes of the gastric mucosa in individuals infected with H. pylori [56 -58].…”
Section: Medical Therapy For Peptic Ulcer and Its Relation To Stomachmentioning
confidence: 99%
“…The fact that patients with pernicious anemia, invariably associated with gastric atrophy and hypochlorhydria, have an increased risk of developing stomach cancer [52,53] has raised the question of whether therapeutic hypochlorhydria is carcinogenic to the stomach. Pharmacologically induced hypochlorhydria has been shown to be associated with increased gastric bacterial growth, reduction of nitrate to nitrite, and increased concentration of carcinogenic N-nitroso compounds in the gastric juice [54,55]. Some studies have indicated that long-term treatment with PPIs may accelerate the development of atrophic changes of the gastric mucosa in individuals infected with H. pylori [56 -58].…”
Section: Medical Therapy For Peptic Ulcer and Its Relation To Stomachmentioning
confidence: 99%
“…Yip et al suggested that the previous use of cephalosporin antibiotics and gastric acid inhibitors are major risk factors for developing ESBLs in CAPD Peritonitis patients [2]. The use of H2 antagonists is associated with increased intragastric bacteria [2,[12][13][14][15]. Gastric acids prevent bacterial colonization in the small bowel and thus prevent intestinal infections.…”
Section: Discussionmentioning
confidence: 99%
“…They are mostly oropharangeal species and very rarely anaerobic [120]. In a systematic review [121], there was an increase of bacteria in gastric juice in 12 out of 13 studies, irrespective of the investigated drug, either H 2 -RAs (cimetidine, ranitidine) [122,123,124,125,126,127,128,129,130,131,132] or PPIs (omeprazole) [118,133,134,135,136,137,138,139]. Growth at the mucosal surface may be detected in about 50% of patients after long-term treatment with any type of effective antisecretory drug [119, 140].…”
Section: Gastric Acid Gi Flora and Infectionmentioning
confidence: 99%